Refining a paradigm of missional leadership - Kirk J. Franklin (Verbum et Ecclesia)
This article explores how the author’s empirical research of ‘leadership clusters’ can be integrated with Nelus Niemandt’s trialogue of church, culture and biblical narrative to produce a concise paradigm of missional leadership. Franklin’s (a student of Niemandt) development of leadership clusters was derived from global missional leaders’ philosophies. To strengthen the biblical foundation, the study explores shepherd-servant-steward metaphors of leadership. Together, these enrich the understanding of (global) missional leadership by highlighting characteristics such as participatory engagement, adaptive responsiveness, relational integrity and transformative action. The integration of biblical models with (global) missional leadership paradigms ensures an integrated approach that aligns with God’s mission while addressing the complexities of globalised contexts.